Identification of Key Genes and Pathways Involved in Circulating Tumor Cells in Colorectal Cancer - Ruijun Pan; Chaoran Yu; Yanfei Shao; Hiju Hong; Jing Sun; Zhou Zhang; Peiyong Li; Minhua Zheng (Analytical Cellular Pathology)
Background. Characterization of the features associated with circulating tumor cells (CTCs) is one of major interests for predicting clinical outcome of colorectal cancer (CRC) patients. However, the molecular features of CTCs remain largely unclear. Methods. For identification of key genes and pathways, GSE31023, contained CTCs from six metastatic CRC patients and three controls, was retrieved for differentially expressed gene (DEG) analysis. Protein-protein interaction networks of DEGs were constructed. Hub genes from the network were prognostic analyzed, as well as the association with tumor-infiltrating immune cells. Results. 1353 DEGs were identified between the CTC and control groups, with 403 genes upregulated and 950 downregulated. 32 pathways were significantly enriched in KEGG, with ribosome pathway as top. The top 10 hub genes were included, including eukaryotic translation elongation factor 2 (EEF2), ribosomal protein S2 (RPS2), ribosomal protein S5 (RPS5), ribosomal protein L3 (RPL3), ribosomal protein S3 (RPS3), ribosomal protein S14 (RPS14), ribosomal protein SA (RPSA), eukaryotic translation elongation factor 1 alpha 1 (EEF1A1), ribosomal protein S15a (RPS15A), and ribosomal protein L4 (RPL4). The correlation between CD4+ T cells and RPS14 (correlation=−0.5) was the highest in colon cancer while CD8+ T and RPS2 (correlation=−0.53) was the highest in rectal cancer. Conclusion. This study identified potential role of ribosome pathway in CTC, providing further insightful therapeutic targets and biomarkers for CRC.